Optimasi Perencanaan Struktur Rangka Batang Menggunakan Metode Matriks Dalam Analisis Struktur - Zebua, Alfred Gunawan (Jurnal Ilmu Teknik Sipil Indonesia, 2026)
Truss structures are widely used in civil engineering design due to their efficiency in transferring loads through axial forces. However, conventional truss designs are often not optimal in terms of material utilization. This study aims to examine the application of the matrix stiffness method in truss structural analysis and to optimize structural design in order to achieve a more efficient configuration. The research methodology employs a numerical analysis based on the matrix stiffness method combined with a deterministic optimization approach. A two-dimensional truss structure model is analyzed to obtain axial forces and nodal displacements, which are then used as the basis for evaluating the objective function of minimizing structural weight under allowable stress and maximum displacement constraints. The results indicate that the application of the matrix method in the optimization process leads to a more uniform stress distribution and a significant reduction in total structural weight without exceeding the allowable strength and serviceability limits. Therefore, the matrix method is proven to be an effective and reliable approach for both analysis and optimization in truss structure design.